Evolution of Phenolic Content, Antioxidant Capacity and Phenolic Profile during Cold Pre-fermentative Maceration and Subsequent Fermentation of Cabernet Sauvignon Red Wine - Muñoz-Bernal, Ã“.A.; Coria-Oliveros, A.J.; Vazquez-Flores, A.A.; de la Rosa, L.A.; Núñez-Gastélum, J.A.; Rodrigo-García, J.; Ayala-Zavala, J.F.; Alvarez-Parrilla, E. (South African Journal of Enology and Viticulture, 2020)
The phenolic compound profile and content of red wines are modified during the maceration-fermentation process by several factors that alter the extractability of the compounds and by reactions that phenolic compounds undergo, and can be directly related to the quality of the final wine and its beneficial effects on the consumer. The aim of this study was to determine the change in phenolic content and profile during cold pre-fermentative maceration and fermentation without the removal of grape pomace. Total phenolics, flavonoids, anthocyanins, tannins and antioxidant capacity were determined by spectrophotometric methods, and the phenolic profile was determined by HPLC-MS on each day of the maceration-fermentation process. The results showed a variation in the content of phenolic compounds and antioxidant activity over time, but the final phenolic content showed no significative difference compared with the initial content (1 268 mg GAE/L and 1 115 mg GAE/L respectively). The phenolic profile showed that flavonoids were the principal compounds in wine and that they increased at the end of the winemaking. Condensed tannins also increased during fermentation, while anthocyanins and some phenolic acids decreased at the end of the process. The final content of phenolic compounds was similar to the initial one, but there was a change in the different fractions of phenolic compounds at the end of fermentation.